Mesopyme-IEMA software process evaluation model for small and medium software industries - Basha, Imran (2014)
The Software Industry plays a prominent role in the economy. During the last few years, many (SPI) methods have been presented to increase the quality of products and services provided by software industries. SPI is generally associated with large scale software organizations because large scale software industries have the capacity to get funding for programs to improve the software process activities widely. Small and Medium (SMI) software industries do not have the same financial opportunities, but still in need of software process improvement programs, to strengthen these small and medium-sized businesses we need to improve current software process in industries. This research will lead to a recommendation of how to conduct the software process evaluation that a SMI can be used to implement improvements and see the benefits at a short time. This research presents a new software process model called Mesopyme-IEMA with the main focus of to reduce effort and time on the SPI implementation and to find a way for SMI to improve the quality of the final product. New model focuses on the improvement in the implementation stage, which is based on a concept called Action Package. The results obtained from SMI by using this new Mesopyme-IEMA action Package model in five industries is also presented in this thesis which proves significant improvement in software process as well as the final products delivered with quality.